Early Treatment Response Predicts Outcome in Paediatric Ulcerative Colitis: GASTROENTEROLOGY: INFLAMMATORY BOWEL DISEASE. Issue 2 (August 2018) - Gasparetto, Marco; Wong-Spracklen, Vivien; Torrente, Franco; Howell, Kate; Brennan, Mary; Noble-Jamieson, Gabriele; Heuschkel, Robert; Zilbauer, Matthias
Abstract : ABSTRACT: The disease course of children with ulcerative colitis (UC) varies substantially. Published data on predictors of disease outcomes in children remain scarce. We validate clinical predictors of outcomes in 93 children with UC in a single centre (age range: 2–18 years, minimum follow-up: 18 months). We stratified children into 3 groups according to their disease course, that is, 1 = mild (38/93, 40.9%), 2 = moderate (38/93, 40.9%), 3 = severe (17, 18.2%). Comparison of clinical and biochemical parameters was performed between groups using Chi-square, Mann-Whitney, and log-rank tests. Predictors of a severe disease course included pancolitis ( P 0.01), low albumin ( P 0.005), low haemoglobin at diagnosis ( P 0.04), paediatric ulcerative colitis activity index (PUCAI) at 3 months, and nonresponse to steroids at 3 months ( P 0.0001). In our cohort, failure to achieve remission at 3 months implied an 80% likelihood to require biologics or major surgery within 18 months. A specific 3-month review point is recommended to guide future management. Abstract : Supplemental Digital Content is available in the text